Association of falls with health-related quality of life (HRQOL) in older cancer survivors: A population based study. Issue 3 (May 2016) - Pandya, Chintan; Magnuson, Allison; Dale, William; Lowenstein, Lisa; Fung, Chunkit; Mohile, Supriya G.
Abstract: Objective: To examine the association between falls and health-related quality of life (HRQOL) in older cancer survivors. Materials and Methods: Using the 2006–2011 Surveillance, Epidemiology, and End Results cancer registry system and the Medicare Health Outcomes Survey (SEER-MHOS) linkage database, a cross-sectional analysis was performed including 17, 958 older cancer survivors. Multivariable regression models were used to evaluate the association of falls with HRQOL measured by the physical component summary (PCS) and mental component summary (MCS) scores on the Veteran RAND 12-item health survey after controlling for demographic, health- and cancer-related factors. A longitudinal analysis using the analysis of covariance (ANCOVA) models was also conducted comparing changes in HRQOL of older cancer survivors who fell with HRQOL of older patients with cancer who did not fall. Results: In the cross-sectional analysis, 4524 (25%) cancer survivors who fell reported a significantly lower PCS (− 2.18; SE = 0.16) and MCS (2.00; SE = 0.17) scores compared to those who did not ( N  = 13, 434). In the longitudinal analysis, after adjusting for baseline HRQOL scores and covariates, patients who fell reported a decline in mean HRQOL scores of both PCS (− 1.54; SE = 0.26) and MCS (− 1.71; SE = 0.27). Presence of depression, functional impairment and comorbidities was significantly associated with lower HRQOL scores. Conclusion: Falls are associated with lower HRQOL scores and are associated with a significant prospective decline in HRQOL in older cancer survivors. Further research is necessary to determine if assessment and intervention programs can help improve HRQOL by reducing the likelihood of falls.